A invenção da primavera: apontamentos sobre o discurso ocidental a respeito das revoltas árabes - Cleto, Murilo Prado (2014)
This scientific work makes a view of the Orient's construction process in west imaginary over History since Greek-Persian War and the first representations from what was qualified as “barbarian” in the Ancient History until the contemporany discourse about the “islamic fundamentalism” through Middle Age concepts, the Modern Age's expanding renaissancist spirit and the illuminist scientism. Under this scenery, the dissertation argues Orientalism's principal unrolling in the production of a western interpretation about the rebellions that shakes arabian world since december 2010.